Blogging with the "New Google Blogger" - Miller, Michael, 1958- (Shortcut, 2006)
Blogging with the New Google Blogger is a digital short cut that covers Google's newest version of Blogger, their free software for creating a website from which to post thoughts, interact with people, and more. This short cut serves as an introduction to the world of blogging and to the Blogger application, as well as a guide to the new version of Blogger. Readers will learn how the new version of Blogger differs from the original version and how to create a Blogger blog. Advanced users will appreciate the information on customizing blog templates, using HTML, hosting their own Blogger blog, syndicating their blogs with RSS and Atom feeds, and making money with blog advertising. Table of Contents Welcome to the Blogosphere A general discussion on blogs--what they are, how they work, and why people blog Introducing the New Version of Blogger Introduction to Blogger; discussion of the new and changed features in the new version of Blogger Launching Your First Blog Detailed step-by-step instructions on how to create a Blogger blog Creating New Blog Posts Posting from the Blogger dashboard, posting from the Google toolbar, categorizing your posts with labels Multimedia and Mobile Blogging Including photos, feeds, and other media in your posts; mobloging from mobile phones Managing Your Blog Using the Dashboard to manage your blog, controlling who can read your blog, creating a private blog, managing comments, examining blog usage statistics Customizing Your Blog Choosing new Blogger templates, customizing templates, adding new page elements, coding non-standard elements with HTML Hosting Your Own Blog Detailed instructions on how to host a Blogger blog on your own website; also covers how to assign a dedicated domain or URL to your blog Syndicating Your Blog Adding RSS and Atom feeds, syndicating the feed, customizing your feed for individual posts or comments Making Money from Your Blog Adding Google AdSense and other advertising to your blog.